A world of social interaction for all. (9th March 2015) - Ferguson, Laura
Abstract : Purpose: – The purpose of this paper is to highlight the actions needed and organisations to make a difference to the problem of loneliness in old age. Design/methodology/approach: – Draws on the work of the Campaign to End Loneliness in collaboration with hundreds of organisations worldwide to document what has been done so far and to provide exemplars and imagined case studies based on collected experience to identify potential relevant actions. Findings: – Many hundreds of organisations worldwide are recognising the need to support older peoples' connections and abilities to engage with their communities. However, these need to be better mapped and coordinated. Practical implications: – Innovative work is already being done to tackle loneliness needs to be more systematically supported and promoted. Originality/value: – Identifies how much has already changed in terms of recognising and addressing loneliness but that a more comprehensive approach to support is needed.